Evaluasi Transparansi dan Realisasi Manajemen Keuangan Sekolah Jenjang SMP Satu Dekade - Hutasoit, Josua Boni; Sidabutar, Ivana Cristin; BR Tarigan, Kezia Elmaesia; Siregar, Uyun Hanip; Hutahaean, Marlon Brando (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study evaluates the transparency and realization of school financial management at the Junior High School (SMP) level over the past decade (2015–2026). Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, 31 national articles from databases such as Google Scholar, Garuda, and SINTA were analyzed. The results indicate a significant paradigm shift from manual-traditional management to a professional, digital-based system, particularly through the adoption of the Application for School Activity Plans and Budgets (ARKAS). While approximately 58% of the reviewed literature shows high levels of transparency involving active stakeholder participation, the actual budget realization still faces structural challenges. The primary obstacles identified include limited human resource competence, administrative complexity, and regulatory rigidity. This study concludes that while transparency has improved, strengthening managerial training and digital infrastructure remains essential to ensure that financial management effectively supports the sustainable improvement of educational quality.